Application of modern coexistence theory to rare plant restoration provides early indication of restoration trajectories. Issue 7 (5th July 2022) - Aoyama, Lina; Shoemaker, Lauren G.; Gilbert, Benjamin; Collinge, Sharon K.; Faist, Akasha M.; Shackelford, Nancy; Temperton, Vicky M.; Barabás, György; Larios, Loralee; Ladouceur, Emma; Godoy, Oscar; Bowler, Catherine; et al.
Abstract: Restoration ecology commonly seeks to re‐establish species of interest in degraded habitats. Despite a rich understanding of how succession influences re‐establishment, there are several outstanding questions that remain unaddressed: are short‐term abundances sufficient to determine long‐term re‐establishment success, and what factors contribute to unpredictable restorations outcomes? In other words, when restoration fails, is it because the restored habitat is substandard, because of strong competition with invasive species, or alternatively due to changing environmental conditions that would equally impact established populations? Here, we re‐purpose tools developed from modern coexistence theory to address these questions, and apply them to an effort to restore the endangered Contra Costa goldfields ( Lasthenia conjugens ) in constructed ("restored") California vernal pools. Using 16 years of data, we construct a population model of L. conjugens, a species of conservation concern due primarily to habitat loss and invasion of exotic grasses. We show that initial, short‐term appearances of restoration success from population abundances is misleading, as year‐to‐year fluctuations cause long‐term population growth rates to fall below zero. The failure of constructed pools is driven by lower maximum growth rates compared with reference ("natural") pools, coupled with a stronger negative sensitivity to annual fluctuations in abiotic conditions that yield decreased maximum growth rates. Nonetheless, our modeling shows that fluctuations in competition (mainly with exotic grasses) benefit L. conjugens through periods of competitive release, especially in constructed pools of intermediate pool depth. We therefore show how reductions in invasives and seed addition in pools of particular depths could change the outcome of restoration for L. conjugens . By applying a largely theoretical framework to the urgent goal of ecological restoration, our study provides a blueprint for predicting restoration success, and identifies future actions to reverse species loss.